Efficient estimation of population mean under stratified random sampling with linear cost function. Issue 12 (2nd December 2021) - , Mradula; Yadav, Subhash Kumar; Varshney, Rahul; Dube, Madhulika
Abstract: The article proposes a ratio estimator of population mean using information on population median of the study variable, which is known under stratified random sampling. The mean square error of the proposed estimator with linear cost function is obtained and a comparative study of the estimator with existing related estimators is carried out. The solution of the problem is achieved with the help of integer programing using Lagrange multiplier technique using both the real data set and the data simulated from a bivariate normal distribution. Both the data sets demonstrate that the proposed estimator is more efficient than the other existing estimators.